2016
DOI: 10.1177/2325967116664685
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Transphyseal Drilling in Skeletally Immature Patients With Anterior Cruciate Ligament Injury

Abstract: Background:Anterior cruciate ligament reconstruction (ACLR) in skeletally immature patients can result in growth plate injury, which can cause growth disturbances.Purpose:To evaluate radiological tibial and femoral length and axis growth disturbances as well as clinical outcomes in skeletally immature ACLR patients treated with a transphyseal drilling technique.Study Design:Cohort study; Level of evidence, 3.Methods:A total of 39 pediatric patients with ACL injury and open physes at time of surgery, as diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
0
33
1
Order By: Relevance
“…14 Iatrogenic physeal damage during ACL reconstruction remains a concern, as the risk for growth arrest and resultant angular and length deformities after an intraoperative physeal injury has been well documented. 6,13,26,34 Because of this risk, several new techniques for ACL reconstruction in the pediatric and adolescent populations have emerged. 1,5,12,15 Although controversy remains about the optimal treatment of pediatric and adolescent ACL injuries, there is consensus emerging that surgical reconstruction is superior to nonoperative treatment in active patients.…”
mentioning
confidence: 99%
“…14 Iatrogenic physeal damage during ACL reconstruction remains a concern, as the risk for growth arrest and resultant angular and length deformities after an intraoperative physeal injury has been well documented. 6,13,26,34 Because of this risk, several new techniques for ACL reconstruction in the pediatric and adolescent populations have emerged. 1,5,12,15 Although controversy remains about the optimal treatment of pediatric and adolescent ACL injuries, there is consensus emerging that surgical reconstruction is superior to nonoperative treatment in active patients.…”
mentioning
confidence: 99%
“…Additionally, despite its history of good to excellent results, more recent data have called into question the safety of transphyseal drilling for patients 2 to 3 years away from achieving skeletal maturity. In a recent study by Fauno et al, 15 24% of patients who underwent transphyseal ACLR experienced either a compensated growth disturbance or leg-length discrepancy of ≥10 mm. Several other studies and reviews have reported premature physeal closure, angular deformities, and leg-length discrepancies with transphyseal ACLR.…”
Section: Discussionmentioning
confidence: 94%
“…Seventy-seven articles reporting the clinical outcomes of pediatric and adolescent patients undergoing ACL reconstruction were analyzed. 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ,…”
Section: Resultsmentioning
confidence: 99%